Move-Tense Interactions in Undergraduate Thesis Abstracts: Pedagogical Insights for EFL Writers - Erzad, Azizah Maulina; Hartono, Rudi; Astuti, Puji; Widhiyanto, Widhiyanto (Institut Agama Islam Negeri Kudus, 2026)
Writing effective thesis abstracts remains a significant challenge for many EFL undergraduates, particularly in organizing rhetorical moves and selecting appropriate verb tenses. This study investigates the interaction between rhetorical move structures and tense usage in undergraduate thesis abstracts in English Education Department, offering a combined genre- and language-focused perspective that remains underexplored in EFL genre research. Using a qualitative Genre-Based Discourse Analysis approach, 41 abstracts from an Indonesian Islamic university were analyzed, with questionnaire data from 7 alumni, to identify common writing difficulties. The analysis applied a five-move model adapted from Swales and Feak, Koopman, and Weissberg and Buker, as well as frameworks for tense distribution. The findings show that although most abstracts successfully include the Aim (92.68%), Method (100%), and Results (97.56%) moves, only 36.59% present a complete five-move structure due to the limited presence of the Conclusion move. Tense analysis reveals an overuse of the present tense across moves, including in the Method (73.2%) and Results (80%) sections, where the past tense is typically required. Questionnaire responses indicate persistent difficulties related to understanding move functions, selecting appropriate tenses, and applying academic writing conventions without explicit guidance. Overall, the study demonstrates partial adherence to conventional abstract-writing practices and highlights the importance of explicit instruction in rhetorical organization and tense selection in EFL academic writing courses to support students’ development as academic writers.